A Study Based On Stigma Experienced by Divorced Women in Pakistan; An Exploratory Research - Noshaba Razaq; Najia Zulfiqar; Amara Gul (JSSH, 2024)
This qualitative study, grounded in phenomenological theory and utilizing semistructured, issue-focused interviews, explores the stigma experienced by divorced women in Pakistan. The study involved 15 women who had experienced stigma after divorce, selected through purposive sampling. Data were analyzed using a grounded theory approach, resulting in 44 initial codes, 19 sub-themes, and 7 main themes. The first theme, "Forms of Stigma Experienced," includes social, familial, and economic stigma, while the second, "Impact on Mental Health and Well-being," encompasses psychological distress, physical health issues, and social isolation. The third theme, "Coping Mechanisms," highlights personal resilience, support systems, and spiritual practices. "Cultural and Religious Influences," the fourth theme, focuses on cultural norms and religious beliefs. The fifth theme, "Barriers to Social and Economic Reintegration," identifies challenges such as employment difficulties, legal and financial barriers, and social acceptance. "Identity and Self-esteem," the sixth theme, explores how divorced women perceive themselves and their public identity. Lastly, the seventh theme, "Strategies for Reducing Stigma," discusses the importance of community awareness, policy reforms, and support services. The findings show that divorced women in Pakistan endure significant stigma, leading to mental and physical health challenges and social isolation. However, they demonstrate resilience through personal growth, support from networks, and spirituality. Cultural and religious norms often hinder their reintegration into society. The study calls for increased community awareness, policy changes, and enhanced support services to reduce stigma and aid divorced women’s reintegration.